Efektifitas Breast Care (Perawatan Payudara) Terhadap Kelancaran Produksi Asi Pada Ibu Post Partum Hari Ke 7 di RSU Saras Ibnu Sina Sukowati Sragen - Siamti Wilujeng; Yuyun Triani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Mother's milk is an important intake for the growth and development and health of babies. The causes of irregular breast milk production include reduced breast milk production on the first day after giving birth due to decreased stimulation of the hormones oxytocin and prolactin which play a role in smooth breast milk production. Therefore, non-pharmacological efforts are needed in the form of breast care. Breast care is useful for facilitating the expulsion reflex and increasing the smooth production of breast milk. The objectives of the research was to determine the effectiveness of Breast Care in smoothing breast milk production in post partum mothers at the Saras Ibnu Sina Sukowati General Hospital, Sragen. Quantitative research type with a quasi-experimental design with a post test-only non-equivalent control group approach. Samples were taken by accident. The samples were 15 people as controls and 15 post partum mothers as the treatment group. Data analysis techniques using Mann Whitney. Result this research that the smoothness of breast milk production for the treatment group was mean ± SD (8.33 ± 0.899) and the control group had a mean ± SD (4.73 ± 0.458). There was an influence of breast care on the smooth production of breast milk in post partum mothers on day 7 (p value 0.000 < 0.05). So that there was an influence of breast care on the smooth production of breast milk in post partum mothers on day 7 at RSU Saras Ibnu Sina Sukowati Sragen